Factors influencing users' perspective on adopting cloud computing framework in higher educational institutions of Bangladesh - Rahman, Mohammad Masudur (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2021)
At present, education has evolved from being confined only to the four walls of a classroom, to a more flexible online learning environment where teachers and students can interact with each other from anywhere, at any time. To date, various studies on the adoption of cloud computing have highlighted the advantages of using cloud computing in HEIs around the world. However, there has been a lack of research in identifying factors that influence cloud computing adoption in HEIs of a developing country as Bangladesh. This study thus investigates the factors that influence the adoption of cloud computing services among university students and faculty members in Bangladesh. The study has adopted a mixed method approach, which involves interviews and a questionnaire survey among 481 students and faculty members in Bangladeshi HEIs. It has used the Statistical Package for Social Sciences (SPSS v.22) and SmartPLS (v3.2.7) software for the analysis of the questionnaire responses. The researcher has designed the conceptual model of the study based on UTAUT model. The findings reveal that perceived benefits (t-value=5.681) and social influences (t-value =2.094) have significant positive influence on the intention to use of cloud computing. In contrast, technophobia (t-value=2.123) and the quality of Internet infrastructure (t-value=3.752) have significant negative effects on the intention behind the actual use of cloud computing. On the other hand, perceived risk, the lack of knowledge and awareness of cloud computing, facilitating conditions, complexities and skills transferability have non-significant influence on the intention of actual use of cloud computing. The study further emphasised that gender has a moderating effect on perceived risk and social influence; Age and experience-moderating variables have a significant impact on the social influence of the hypothesised relationships in the proposed research model. The results of this study will help policymakers of Bangladeshi HEIs in ensuring effective adoption of cloud services by faculty members and students. Moreover, the study sets an example for other developing countries in the world by highlighting the factors that influence cloud computing adoption among faculty members and students in HEIs.